2018
DOI: 10.1126/scitranslmed.aao4097
|View full text |Cite
|
Sign up to set email alerts
|

A bioengineered retinal pigment epithelial monolayer for advanced, dry age-related macular degeneration

Abstract: Retinal pigment epithelium (RPE) dysfunction and loss are a hallmark of non-neovascular age-related macular degeneration (NNAMD). Without the RPE, a majority of overlying photoreceptors ultimately degenerate, leading to severe, progressive vision loss. Clinical and histological studies suggest that RPE replacement strategies may delay disease progression or restore vision. A prospective, interventional, U.S. Food and Drug Administration-cleared, phase 1/2a study is being conducted to assess the safety and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
293
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(298 citation statements)
references
References 33 publications
2
293
0
3
Order By: Relevance
“…Transplantation of stem cell-derived RPE has emerged as a possibility for treating AMD (12,13), and clinical trials are currently underway (e.g. (14)(15)(16)(17)(18)). An unexplored complementary approach is the development of therapies that stimulate endogenous RPE regeneration.…”
Section: /Body Introductionmentioning
confidence: 99%
“…Transplantation of stem cell-derived RPE has emerged as a possibility for treating AMD (12,13), and clinical trials are currently underway (e.g. (14)(15)(16)(17)(18)). An unexplored complementary approach is the development of therapies that stimulate endogenous RPE regeneration.…”
Section: /Body Introductionmentioning
confidence: 99%
“…The progress in human development knowledge and the refinement in hPSC culture and differentiation protocols have brought hPSC cells and their derivatives into the first clinical trials for several diseases, including AMD. [15][16][17][18][19][20] As the use of hPSC and/or their derivatives is reaching patients, multiple efforts are put together aiming to develop tests to assess the safety of the stem cell-derived products. Several groups have shown that hPSC may acquire genetic and/or epigenetic mutations during their culture or differentiation, 26,52 raising some concerns about their use in future cell therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Kashani et al transplanted 3.5 mm × 6.25 mm sheets of hESC‐derived RPE monolayers into areas of GA in five AMD patients . Since RPE cells are lacking in areas of GA, these experiments explicitly replace lost native RPE in the area of GA.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…There was no correlation between the presence of postoperative pigmentation and postoperative visual improvement, nor did the absence of hyperpigmentation preclude visual improvement. Kashani et al transplanted 3.5 mm × 6.25 mm sheets of hESC-derived RPE monolayers into areas of GA in five AMD patients [36]. Since RPE cells are lacking in areas of GA, these experiments explicitly replace lost native RPE in the area of GA.…”
Section: Rpe Transplantation For Ga In Amdmentioning
confidence: 99%
See 1 more Smart Citation